STUDENTS’ RESPONSES TO THE USE OF WORDWALL AS A LEARNING MEDIA FOR NEWS TEXTS IN JUNIOR HIGH SCHOOL - Lutfi'ah, Ajeng Lintang; Susilo, Jimat (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This research is motivated by the low interest and learning outcomes of students in understanding news text material in class VII G, which is caused by the use of conventional learning media that is less interesting. The purpose of this study is to describe student responses in improving student learning outcomes in news text material. This study uses a qualitative method with a descriptive approach. The subjects of the study were 24 students in class VII G. Data were collected through an open questionnaire that was analyzed qualitatively to determine student responses to the use of Wordwall. The results showed that the majority of students gave positive responses to Wordwall media. They felt that learning was more fun, interactive, and easy to understand. This media is also able to increase student motivation and concentration during learning. In addition, students feel more challenged and motivated to answer practice questions because of its attractive appearance and competitive scoring system. The conclusion of this study is that the use of Wordwall as an interactive learning media is effective in increasing student interest and understanding of news text material. Therefore, teachers are advised to utilize digital media such as Wordwall as an alternative in a creative and innovative learning process.